EXPLORING THE DYNAMICS OF SECESSIONIST SENTIMENTS IN ALASKA - Ario Bimo Utomo (Universitas Gadjah Mada, 2019)
This article explores the dynamics of secession in Alaska, a state within the United States of America. Alaska has been an integral part of modern American history when it was admitted as the second-youngest state after Hawaii in 1959. The territory was initially purchased by the United States from the Russian Empire in 1867 due to the latter’s concern of the expected British invasion. Putting the colonial narratives aside, Alaska is also a home of the Indigenous Alaskans with distinct identities compared to the European settlers. Viewing this contested history, combined with controversies leading to the inclusion of Alaska to the United States proper, one might assume that Alaskans might possess a higher sentiment of self-determination compared to the rest of Americans. However, despite those backgrounds, secessionism is not a salient issue in Alaska. Therefore, the author explores why the support for Alaskan secessionism is relatively unheard of despite the disputed history of the state. Using Hechter’s model of secession (1992), the author proposes that Alaska has been experiencing a relatively low level of secessionist sentiment due to (1) a low level of group identification among the Alaskans themselves, (2) a weak regional party, (3) a high level of economic dependency on the host state, and (3) an unfavorable institutional environment for secessionist sentiments to be advanced. The research concludes by suggesting that secessionism in Alaska is not a favorable choice due to every limitation it faces.Keywords: AIP; Alaska; history; postcolonialism; secession